Advantages of using artificial intelligence tools in the press media (Islas, 2024)
In this work we are going to analyze which are the applications of artificial intelligence that can be used effectively in a press medium. to do this, we use bibliographic review, analysis and synthesis to learn about best practices and summarize them. we will present real results from other media outlets and how they could be applied to ours. we will also show a series of examples of applications that our communicators can use.
Keywords: intelligence; artificial; media; communication; press; technology; digital